Mo@ZIF-8 nanozyme preparation and its antibacterial property evaluation - Lian, Zheng; Lu, Chunqing; Zhu, Jiangqi; Zhang, Xining; Wu, Ting; Xiong, Youlin; Sun, Zhiyi; Yang, Rong (Frontiers in Chemistry, 2022)
Types of nanozymes can produce free radicals and/or reactive oxygen species (ROS) to serve as broad spectrum antibacterial materials. Developing nanozyme-based antibacterial materials with good biocompatibility exhibits promising application prospects. In this study, we doped Mo to ZIF-8 (both components have good biocompatibility) to prepare a new nanozyme, Mo@ZIF-8, which can produce hydroxyl radicals (•OH) triggered by a low dosage of hydrogen peroxide (H2O2), exhibiting effective antibacterial capability against both Gram-negative bacteria (Escherichia coli) and Gram-positive bacteria (Staphylococcus aureus). This work provides a reference for the design of antibacterial nanozymes with good biocompatibility.